Oligo-thiophene tethered 1, 10-phenanthroline as N-chelating moiety. Electrochemical and optical characterization of the π-conjugated molecule and of the relevant conducting polymer and metallopolymers. (15th January 2015) - Manca, Paola; Gladiali, Serafino; Cozzula, Daniela; Zucca, Antonio; Sanna, Gavino; Spano, Nadia; Pilo, Maria I.
Abstract: The synthesis and characterization of a new highly conjugated molecule, 4-(2, 2':5′, 2″-terthien-3'-ethynyl)-1, 10-phenanthroline (TAF4) is reported. The new compound features an expanded π-conjugation as compared with the analogue 2, 2′:6′, 2″-terpyridine derivative (4'-(2, 2':5′, 2″-terthien-3'-ethynyl)-2, 2':6′, 2″-terpyridine) we have recently reported. The electrochemical polymerization of TAF4 allows to obtain the corresponding conducting polymer PTAF4. Electrochemical and spectroscopic characterization were performed on both the original tether TAF4 and the polymer, and the results are compared with related structures bearing different spacers and nitrogen substituents. PTAF4 shows a remarkable lowering of band gap value that is consequent on the nature both of the spacer and of the substituent on the terthiophene fragment. Furthermore, the synthesis and characterization of the Ru(II) complex, [Ru(TAF4)3 ][PF6 ]2, and of the corresponding metallopolymers, are reported. Graphical abstract: Highlights: Unsymmetric substitution in 4 position on 1, 10-phenanthroline with oligo-thiophene. Ethynylated bridge between the terthiophene and the phenanthroline fragment. p- and n-doping of the corresponding conducting polymer. Anodic and (unusual) cathodic polymerization of the corresponding Ru(II) complex. Outer-sphere metallopolymers.